Manajemen Sarana Prasarana SMK BLUD di Daerah Istimewa Yogyakarta - Sukarman Sukarman; Maria Dominika Niron (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The management of educational facilities and infrastructure constitutes a critical component in enhancing the quality of the learning process in Vocational High Schools (SMKs), particularly those implementing the Regional Public Service Agency (Badan Layanan Umum Daerah/BLUD) financial management system. This study aims to examine the implementation of facilities and infrastructure management, identify the challenges encountered, and analyze the strategies employed to overcome these challenges in BLUD-based SMKs in the Special Region of Yogyakarta. This research employed a descriptive qualitative approach and was conducted at SMK Negeri 1 Sewon, SMK Negeri 2 Pengasih, and SMK Negeri 3 Wonosari. Data were collected through in-depth interviews, direct observations, and document analysis, and were analyzed using the interactive analysis model developed by Miles and Huberman. The results indicate that the management of facilities and infrastructure in BLUD-based SMKs has been implemented in a planned and systematic manner in accordance with the technical guidelines issued by the Department of Education, Youth, and Sports. The management process encompasses planning, procurement, inventory control, utilization, and asset disposal. The involvement of business and industry sectors in the planning stage plays a strategic role in ensuring the alignment of graduates’ competencies with labor market demands. However, several constraints were identified, including limitations on equipment specifications due to Domestic Component Level (Tingkat Komponen Dalam Negeri/TKDN) regulations, the suboptimal involvement of industry partners in certain areas of expertise, and relatively lengthy asset disposal procedures. These challenges are addressed by strengthening industry partnerships, selecting suppliers that comply with regulatory requirements, and optimizing the management of temporary storage facilities.